Assessing the effects of logging activities on avian richness and diversity in different aged post-harvested hill dipterocarp tropical rainforest of Malaysia - Rajpar, Muhammad Nawaz; Hussin, Mohamed Zakaria (Science Publications, 2014)
Logging activities have encroached into the hill dipterocarp tropical rainforest area since the lowland dipterocarp forests have decreased in size. Hill dipterocarp tropical rainforest is rich in habitat diversity and provide a variety of resources for avian species such as food, habitat and shelter. Therefore it is important to examine the logging effects of hill dipterocarp rainforest on avian species. We compared the avian richness and diversity in different aged post-harvested hill dipterocarp tropical rainforest at the Berkelah Hill Dipterocarp Rainforest Reserve in Maran, Pahang, West Malaysia using mist-netting method. We captured a total of 1908 individuals representing 86 species and 29 families (i.e., 18.55% from two years post-harvested forest, 25.10% from ten years post-harvested, 23.90% from twenty years post-harvested and 32.44% from thirty five years post-harvested forests). Forty nine species were caught in two years and ten years, 55 species in twenty years and 59 species in thirty five years post-harvested forest. Seventeen species were common in all four types of forest. Pycnonotidae, Timaliidae and Nectariniidae were the most dominant families in all types of post-harvested hill dipterocarp tropical rainforest. Diversity analysis indicated that the bird species in twenty years post-harvested hill dipterocarp rainforest was most diverse (i.e., Fishers Alpha Diversity Index; 16.34) and evenly distributed (i.e., McIntosh Evenness index E; 0.933) as compared to two years, ten years and thirty five years post-harvested forest. However, thirty five years post-harvested forest was richest in avian species (i.e., Margalefs Richness index R1; 9.02) as compared to other post-harvested forest. The findings of this study revealed that logging and recovery process may affects on avian distribution and diversity. However, these effects may vary from species to species.